Application of Digital Tools Assessing Information Risk in the Control Activity - Kostova, Silviya; Zhelev, Zhelyo (Naše gospodarstvo/Our economy, 2024)
The paper discusses digitising the leading information flows in control activities. The focus is on applying technology and its integration in implementing forms of control. The aim is to argue for practical approaches to minimise information risk in pre-ongoing and post-control to ensure the accuracy and veracity of financial and non-financial information. Evaluating the effectiveness of data ensures integrity, consistency, validity, completeness and timeliness - applying digital risk assessment tools to control activities. To prove the hypotheses, the cross-tabulation method is applied, focusing on the relationship between the use of verification, inspection, audit, revision and supervision, and the digital tools applied in the control institutions implementing financial control in the public sector of the Republic of Bulgaria. The study evaluates the effectiveness of data management practices, emphasizing the importance of maintaining integrity, consistency, validity, completeness, and timeliness. The study acknowledges that the use of advanced digital risk assessment tools could improve the effectiveness of control activities in various areas. The approach supports the sustainability of financial control and is in line with modern management standards, promoting a culture of accountability and precision in the management of public finances.